The effects of short-term resistance training on endocrine function in men and women - Kraemer, W. J.; Staron, R. S.; Hagerman, F. C.; Hikida, R. S.; Fry, A. C.; Scott, A.; Nindl, B. C.; Gothshalk, L. A.; Volek, J. S.; Marx, J. O.; Newton, R. U.; Häkkinen, K. (European Journal of Applied Physiology, 1998)
This investigation examined hormonal adaptations to acute resistance exercise and determined whether training adaptations are observed within an 8-week period in untrained men and women. The protocol consisted of a 1-week pre-conditioning orientation phase followed by 8 weeks of heavy resistance training. Three lower-limb exercises for the quadriceps femoris muscle group (squat, leg press, knee extension) were performed twice a week (Monday and Friday) with every other Wednesday used for maximal dynamic 1 RM strength testing. Blood samples were obtained pre-exercise (Pre-Ex), immediately post-exercise (IP), and 5?min post-exercise (5-P) during the first week of training (T-1), after 6 weeks (T-2) and 8 weeks (T-3) of training to determine blood concentrations of whole-blood lactate (LAC), serum total testosterone (TT), sex-hormone binding globulin (SHBG), cortisol (CORT) and growth hormone (GH). Serum TT concentrations were significantly ( P?=?0.05) higher for men at all time points measured. Men did not demonstrate an increase due to exercise until T-2. An increase in pre-exercise concentrations of TT were observed both for men and women at T-2 and T-3. No differences were observed for CORT between men and women; increases in CORT above pre-exercise values were observed for men at all training phases and at T-2 and T-3 for women. A reduction in CORT concentrations at rest was observed both in men and women at T-3. Women demonstrated higher pre-exercise GH values than men at all training phases; no changes with training were observed for GH concentrations. Exercise-induced increases in GH above pre-exercise values were observed at all phases of training. Women demonstrated higher serum concentrations of SHBG at all time points. No exercise-induced increases were observed in men over the training period but women increased SHBG with exercise at T-3. SHBG concentrations in women were also significantly higher at T-2 and T-3 when compared to T-1 values. Increases in LAC concentrations due to exercise were observed both for men and women for all training phases but no significant differences were observed with training. These data illustrate that untrained individuals may exhibit early-phase endocrine adaptations during a resistance training program. These hormonal adaptations may influence and help to mediate other adaptations in the nervous system and muscle fibers, which have been shown to be very responsive in the early phase of strength adaptations with resistance training.